Influence of digital media on student practice of the faculty of philosophy, letters and educational sciences - Loor-Saltos, Karla Nicole; Bravo-Barrezueta, Silvia Lorena (International research journal of management, IT and social sciences, 2022)
The objective of this study is to determine the influence of digital media on student practice at the Faculty of Philosophy, Letters and Sciences of Education, given that it is of vital importance to guarantee that the infrastructure of digital media, keeping up with the current development of teaching and learning, in addition, educators and students should be encouraged to enjoy more in the use of these tools. The methodology applied in the research is descriptive, exploratory, field, and explanatory, with a mixed approach, that is, qualitative and quantitative, a structured survey was applied on a Likert scale, applied to 245 students. A high reliability of 0.842 was obtained through the SPSS statistic, which shows that digital media have an influence on student practice, generating benefits in the learning-teaching process.